The Design of Emission Taxes in Markets with New Firm Acquisitions - Gautier, Luis; Fikru, Mahelet G. (Springer, 2024)
In the 1990s there was a great deal of interest in the study of the role of endogenous market structure under oligopoly in the characterization of emission taxes. This interest was instrumental in providing policy guidance on the design of emission taxes based on market characteristics. However, the literature has been silent on offering policy recommendations on the design of emission taxes under endogenous market structure in the presence of new firm acquisitions. We build a model where new firms enter the market where some are acquired by an incumbent multi-plant firm, altering the initial market structure. In this framework, we characterize the second-best emission tax and examine the role of the resulting market structure, in particular the role of acquiring more/fewer of the new firms, in the optimal design of emission tax. We argue that, under certain conditions, the acquisition of new firms may lead to higher taxation consistent with the Pigouvian rule or even exceed marginal damages. Our contribution is at the intersection of emission tax design and M &A (new firm acquisition) literature.
Keywords: Impuestos ambientales; Contaminación - Control; Emission tax; Pollution abatement; Start-ups; Free entry and exit; M&A